1969
DOI: 10.1002/cber.19691020917
|View full text |Cite
|
Sign up to set email alerts
|

Die Flavonglykoside von Veronicastrum sibiricum Pennell var. japonicum Hara und Synthese des Luteolin‐7‐neohesperidosids (Veronicastrosid)

Abstract: Aus dem Kraut von Veronicastrum sibiricum Pennell var. japonicum Hara wurde neben Luteolin‐7‐β‐D‐glucopyranosid (1) das bisher noch nicht bekannte Luteolin‐7‐β‐neohesperidosid (2) (Veronicastrosid) isoliert und identifiziert. Zum Strukturbeweis wurde 2 durch Kondensation von Phloracetophenon‐4‐β‐neohesperidosid mit Protocatechualdehyd über 9 synthetisiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Modern pharmacological studies have shown that Veronicastrum species have versatile beneficial pharmacological properties, such as anti-inflammatory, analgesic, antibiosis and immunosuppressive activities (Gao et al, 2004;Huang et al, 2009;Zhou & Meng, 1992a). Several kinds of chemical constituents have been isolated from these plants, including flavonoids, phenols, phenylpropanoids and terpenoids (Inouye & Aoki, 1968;Inouye et al, 1969;Lin et al, 1995;Liu et al, 1999;Nohara et al, 2010;Shang et al, 1997;Shimada et al, 1971;Zhao & Shi, 2007;Zhou & Meng, 1992b). Recently, several studies revealed that Veronicastrum axillare exhibited potential antiulcer effects on gastric ulcer in rats induced by ethanol (Du et al, 2013;Shen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacological studies have shown that Veronicastrum species have versatile beneficial pharmacological properties, such as anti-inflammatory, analgesic, antibiosis and immunosuppressive activities (Gao et al, 2004;Huang et al, 2009;Zhou & Meng, 1992a). Several kinds of chemical constituents have been isolated from these plants, including flavonoids, phenols, phenylpropanoids and terpenoids (Inouye & Aoki, 1968;Inouye et al, 1969;Lin et al, 1995;Liu et al, 1999;Nohara et al, 2010;Shang et al, 1997;Shimada et al, 1971;Zhao & Shi, 2007;Zhou & Meng, 1992b). Recently, several studies revealed that Veronicastrum axillare exhibited potential antiulcer effects on gastric ulcer in rats induced by ethanol (Du et al, 2013;Shen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%